(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: The authors investigated the antioxidant properties of the gel with tricolor violet extract when used in rats with an experimental pаrodontitis model. To simulate periodontal pathology, white laboratory rats were given a solution of ethylenediaminetetraacetic acid (2%) daily with drinking water and three times a week; the drug "Warfarin Orion" was administered per os for 30 days. Animals were randomly divided into four equal groups of 10 each. Group 1 - intact rats; group 2 - rats with a model of pаrodontitis; group 3 - rats with a model and applications on the mucous membrane of the alveolar process gel "Placebo". Group 4 - rats with a pаrodontitis model and applications on the mucous membrane of the alveolar process of the gel with the violet extract. In periodontal tissues and blood serum, we studied the level of inflammation markers - malondialdehyde (MDA) and diene conjugation. The state of the antioxidant defense system (AODS) was also assessed by the activity of glutathione peroxidase (GP), glutathione reductase (GR), glucose-6-phosphate dehydrogenase (G-6-PD), superoxide dismutase (SOD), and catalase. The pаrodontitis model in rats of the 2nd group was characterized by the development of inflammatory processes in periodontal tissues and blood, which is confirmed by changes in the pro- and antioxidant protection system. In rats of the 4th group, the content of MDA was restored in periodontal tissues. The state of the AOP system was normalized (decrease in the activity of SOD and catalase to the values of group 1), the tension in the glutathione-antioxidant defense system disappeared (the activity of GP decreased, and the activity of GR and G-6-PDH increased to the level control). In the blood serum, the content of MDA significantly reduced, and the level of DC remained higher than in group 1.In contrast, stabilization of the activity of marker enzymes of glutathione-antioxidant protection in blood serum (GP, GR, G-6-PDH) was noted with significant activation of the activity of SOD and catalase, with stabilization of SOD and catalase. Conclusion. The periodontal protective effectiveness of the gel with tricolor violet was established, as evidenced by the restoration of the state of protective antioxidant systems and the inhibition of lipid peroxidation processes both directly in the periodontal tissues and at the system level. Keywords: experimental pаrodontitis, lipid peroxidation, antioxidant protection, gel with tricolor violet.